Quorum-quenching enzyme Est816 assisted antibiotics against periodontitis induced by Aggregatibacter actinomycetemcomitans in rats - Wang, Junmin; Ju, Tianjuan; Guo, Lifeng; Shan, Wenwen; Wu, Qianxia; Zhang, Haichuan; Zhang, Jing (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction: Quorum-quenching enzyme Est816 hydrolyzes the lactone rings of Nacyl homoserine lactones, effectively blocking the biofilm formation and development of Gram-negative bacteria. However, its applications in the oral field is limited. This study aimed to evaluate the efficacy of enzyme Est816 in combination with antibiotics against periodontitis induced by Aggregatibacter actinomycetemcomitans in vitro and in vivo.The antimicrobial efficacy of enzyme Est816 in combination with minocycline, metronidazole, and amoxicillin was determined using the minimum inhibitory concentration test. The anti-biofilm effect of enzyme Est816 was assessed using scanning electron microscopy, live/dead bacterial staining, crystal violet staining, and real-time quantitative PCR. Biocompatibility of enzyme Est816 was assessed in human gingival fibroblasts (HGF) by staining. A rat model of periodontitis was established to evaluate the effect of enzyme Est816 combined with minocycline using micro-computed tomography and histological staining.Results: Compared to minocycline, metronidazole, and amoxicillin treatment alone, simultaneous treatment with enzyme Est816 increased the sensitivity of biofilm bacteria to antibiotics. Enzyme Est816 with minocycline exhibited the highest rate of biofilm clearance and high biocompatibility. Moreover, the combination of enzyme Est816 with antibiotics improved the antibiofilm effects of the antibiotics synergistically, reducing the expression of the virulence factor leukotoxin gene (ltxA) and fimbria-associated gene (rcpA). Likewise, the combination of enzyme Est816 with minocycline exhibited a remarkable inhibitory effect on bone resorption and inflammation damage in a rat model of periodontitis.The combination of enzyme Est816 with antibiotics represents a prospective anti-biofilm strategy with the potential to treat periodontitis.